My cousin Maria Schneider a memoir - Schneider, Vanessa 1969- (Scribner, 2023)
A memoir and tribute to the late French actress, best known for playing Jeanne in the controversial film Last Tango in Paris, shows how this role led her to live the rest of her life plagued by scandal, revealing how exploitation has lingering effects that can reverberate through a lifetime
"Originally published in France in 2018 by Éditions Grasset & Fasquelle as Tu t'appelais Maria Schneider" -- From title page verso
Keywords: Schneider, Maria -- 1952-2011; Actors; Motion picture actors and actresses / France / Biography; Schneider, Maria / 1952-2011; Motion picture actors and actresses; France; Biografier; Skådespelare; Biographies; Erlebnisbericht